Growth with financial stability central banking in an emerging market - Mohan, Rakesh 1948- (Oxford University Press, 2011)
It is widely believed that the Indian economy witnessed near stagnation in real GDP growth from Independence till the late 1970s. Challenging this notion, the collection of papers and speeches in this volume provides fresh perspectives on India's growth experience from Independence to the recent global financial crisis. This volume documents how the conduct of Indian monetary and financial policy has been unorthodox by the standards of extant international conventional wisdom, but appropriate to the macroeconomic and structural conditions prevailing in India. With a focus on growth drivers and financial stability, the volume deals with a wide-range of issues: growth of manufacturing and service sectors, role of policies (monetary, fiscal, financial market and sector, external sector), urban infrastructure investment, public service delivery, role of central banks, and the interaction between international finance and monetary policy. Drawing upon the post-reform experience and the global crisis, the volume takes stock of current challenges and suggests strategies to sustain long-term double-digit growth rates.